Synthesis and biological activities of some novel triazoloquinazolines and triazinoquinazolines containing benzenesulfonamide moieties - Ghorab, Mostafa M; Ismail, Zienab H; Abdala, Mohamed (Arzneimittelforschung, 2010)
The reactivity of methyl-2-isothiocyana-tobenzoic acid 2 towards nitrogen nucleophiles was investigated. When compound 2 was reacted with sulfanilamide and/or sulfacetamide the thioureido derivatives 3 and 4 were obtained. Refluxing of compound 3 or 4 with hydrazine hydrate in ethanol afforded the N-amino-quinazoline derivatives 5 and 6, respectively. When compound 5 was reacted with aromatic aldehydes in ethanol, the novel Schiff's bases 7–9 were produced. In a similar manner, aromatic aldehyde were reacted with compound 6 in acetic acid containing fused sodium acetate to furnish the triazoloquinazoline derivatives 10–13. Also, triazoloquinazoline derivative 14 was obtained via reaction of compound 6 with acetic anhydride. In addition, the corresponding triazinoquinazoline derivative 16 was obtained vi reaction of compound 6 with ethyl chloroacetate. The triazoloquinazoline 19 was obtained in good yield via the reaction of 6 with diethyloxalate. Moreover some of the newly synthesized compounds showed good antipyretic and anti-inflammatory activities.
Keywords: Quinazolines, antipyretic and anti-inflammatory activities; Sulfonamide moiety